OVERCOMING SLUM SETTLEMENTS: LESSON LEARNED FROM IMPLEMENTATION OF UNINHABITABLE HOUSE SOCIAL REHABILITATION PROGRAM IN SURABAYA - Ekky Fiorentina Asterix; Antun Mardiyanta; Erna Setijaningrum (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Slum areas can generate bad impacts on health and the environment. Thus, the government of Surabaya city arranges TAHU PANAS innovation through a social rehabilitation program for unfit for habitation to overcome. The program has achieved good output. This is evidenced by an increase in program beneficiaries every year, a decrease in the percentage of slum areas, and an award from the Ministry of PANRB as an outstanding innovation. This research aimed to determine and describe the success of the implementation process of this program in overcoming slum settlements in Surabaya city. The success of this implementation can be understood by the theory of policy implementation by Hill & Hupe as an analysis tool. We used qualitative methods through document analysis to discuss these issues. The results showed that the implementation process seen from the characteristics of the policy was optimal because the level of ambiguity and conflict was low; policy formation is adequate in terms of policy objectives, policy standards or targets, human and financial resources as well as incentive policies; the policy transfer process is quite clear and detailed; the effect of the implementor response is quite optimal both in terms of disposition and behavior; horizontal relations between organizations are adequate; positive target group response; and the policy environment that has supported the running of the policy. The implementation process in this program to tackle slum settlements in the city of Surabaya is optimal enough, thus, successful implementation can be achieved.